Spectroscopic investigations, concentration dependent SERS, and molecular docking studies of a hydroxybenzylidene derivative - Kumar, Veena S; Mary, Y Sheena; Mary, Y Shyma; Krátký, Martin; Vinsova, Jarmila; Baraldi, Cecilia; Roxy, M S; Gamberini, Maria Cristina (Journal of biomolecular structure & dynamics, 2022)
Spectroscopic analysis, density functional theory (DFT) studies and surface enhanced Raman scattering (SERS) of (E)-N'-(5-chloro-2-hydroxybenzylidene)-4-trifluoromethyl) benzohydrazide (CHTB) have been studied on different silver colloids in order to know the particular chemical species responsible for the spectra. Very significant shifts are observed for Raman and SERS wavenumbers. Observed changes in the υ-ring modes may be due to surface interaction of the π-electrons and the presence of this suggested that RingII is more tilted in both cases than RingI and the molecule assumes a tilted orientation for the concentration 10-3 M. Orientation changes are seen in concentration dependent SERS spectra. The molecular electrostatic potential has also been constructed to determine the electron rich and poor site of CHTB. The molecular docking studies indicate that the binding affinity and hydrogen bond interactions with the receptors may be supporting evidence for further studies in designing other pharmaceutical applications of CHTB.Communicated by Ramaswamy H. Sarma.
Keywords: Electrons; Hydrogen Bonding; Spectrum Analysis, Raman; hydroxybenzylidene; Ramanova spektroskopie; vodíková vazba; MEP; Molecular Docking Simulation; DFT; docking; Static Electricity; simulace molekulového dockingu; elektrony; SERS; statická elektřina